POLA PEMUKIMAN MASA DEPAN MASYARAKAT PENGEMBARA LAUT, SUKU BAJAU - Vincent Moyola Ancung; Sutarki Sutisna (Jurusan Arsitektur dan Perencanaan, 2021)
In the era of globalization, Nusantara have lost most of its identity and culture. The view of society that has experienced gentrification needs to be restored to raise the locality again. Our minds have been blinded to the standard of living, it's time for us to think again to save the remaining culture. This project is the reflection of the process that has happened, creating another option of a new habitual pattern in the future by taking the literature on the life of the Bajau people, the Sama tribe who partly still embrace their original identity, For centuries the Bajau have lived according to the wind. and ocean currents, but now they are considered as violating national borders until they were arrested 6 years ago, November 2014 because they are considered as foreign and illegal fishermen. They are persuaded and forced to settle on the mainland in order to have an identity, even though their true identity is sea nomads. The story of